Preliminary impact of the adoption of the Icelandic Prevention Model in Tarragona City, 2015–2019: A repeated cross-sectional study - Meyers, Caine C. A.; Mann, Michael J.; Thorisdottir, Ingibjorg Eva; Ros Garcia, Patricia; Sigfusson, Jon; Sigfusdottir, Inga Dora; Kristjansson, Alfgeir L. (Frontiers in Public Health, 2023)
Background There is a great need for effective primary prevention intervention strategies to reduce and delay onset of adolescent substance use. The Icelandic Prevention Model (IPM) showed great success in Iceland over the past twenty plus years, however, evidence for the transferability of model is still somewhat limited. Using data collected in Tarragona during regional efforts to begin adoption of the IPM in Catalonia, this study tested the transferability and stability of the core risk and protective factor assumptions of the IPM over time and examined trends of lifetime smoking, e-cigarette-use, alcohol-use, intoxication, and cannabis-use within the same period. Methods This study includes responses from 15-and-16-years-olds from two region-wide samples taken in 2015 and 2019 in Tarragona (N=2867). Survey questions assessed frequency of lifetime: smoking, e-cigarette-use, alcohol-use, intoxication, and cannabis-use, and the core model assumptions. Demographic data were also collected. Logistic regression models of main effects with and without time interaction were used to test assumptions and their stability across time. Chi-square tests and Wilcoxon-Mann-Whitney U tests were used to compare prevalence of substance use and mean scores of primary prevention variables respectively. Results Lifetime: smoking (-7%, p<0.001) and cannabis-use (-4%, p<0.001) decreased, and e-cigarette-use increased (+33%, p<0.001) in Tarragona. Lifetime intoxication (-7%, p<0.001) decreased in a single zone exclusively. Most core model assumptions held in their hypothesized direction across time. The strongest positive association was observed between time spent with parents during weekends and reduced odds of lifetime smoking (OR: 0.62, 95%CI: 0.57-0.67) and the strongest negative association was observed between being outside after midnight and increased odds of lifetime intoxication (OR: 1.41, 95%CI: 1.32-1.51). Mean scores of primary prevention variables also changed disproportionately in Tarragona. Conclusion This study confirms that the core IPM assumptions are similar in Tarragona as in Iceland and other contexts previously examined. They also indicate that prevalence of lifetime smoking, intoxication, and cannabis-use decreased disproportionately in Tarragona between 2015 and 2019 during the first phase of regional adoption of the model. Thus, targeting model assumptions represents a viable primary prevention strategy for communities that hope to reduce smoking, alcohol-use, intoxication, and cannabis-use among adolescents.